Profile of the genomic characteristics and comparative studies of five Trichiuridae species by genome survey sequencing - Song, Na; Zhao, Xiang; Cai, Chuangeng; Gao, Tianxiang (Frontiers in Marine Science, 2022)
Trichiuridae fish are economically important species and are widely distributed across the nearshore to the open ocean. In the present study, the genomic survey sequencing method was used to analyze the genomic characteristics of five Trichiuridae fish. The calculated genome size was 913 Mb, 868 Mb, 871 Mb, 747 Mb, and 670 Mb for Trichiurus japonicus, Trichiurus nanhaiensis, Trichiurus brevis, Lepturacanthus savala, and Eupleurogrammus muticus, respectively. The average GC content of the five Trichiuridae fish ranged from 39.59% to 42.05%, and the repeat sequence content ranged from 33.21% to 45.87%. The heterozygous ratio of E. muticus was the highest, and that of L. savala was the smallest. The proportion of microsatellite motifs showed a decreasing trend with the increase in repeat numbers: the dinucleotide repeats were dominant, followed by the trinucleotide repeats, tetranucleotide repeats, pentanucleotide repeats, and hexanucleotide repeats. The mitochondrial genomes of five Trichiuridae species were excavated from the genome data, and the ML tree revealed that T. japonicus, T. nanhaiensis, T. brevis, L. savala, and E. muticus formed into one clade. E. muticus showed earlier expansion than the other four species and had a significant population decline at the Last Glacial period by pairwise sequentially Markovian coalescent (PSMC) analysis. This is the first report to sequence and characterize the whole genomes of five Trichiuridae species.